Perancangan Interior Honda CBR Club Surabaya - Sopater Stephen; I Gusti Ngurah Ardana; Grace Mulyono (Intra, 2016)
Interior design of Honda CBR Club Surabaya is a public building that has a facility as a gathering place for fans and visitors, especially Honda CBR brand. This design aims to provide facilities to the fans and community about information around Honda CBR product derived from the Japanese domestic. The main facility of this Club is the Club Bar and café, and supporting facilities including exhibition space, detailing, workshop, etc.